2015
DOI: 10.1002/app.41999
|View full text |Cite
|
Sign up to set email alerts
|

The crosslinking of poly (ether ether ketone): Thermally and by irradiation

Abstract: Crosslinking of amorphous poly (ether ether ketone) films was carried out by means of thermal annealing at 400 C as well as by irradiation with 11.0 MeV proton beam at different dose rate ranging from 1.75 to 15.5 kW g 21. The materials properties of the resulting films were investigated by mean of light microscopy, sol-gel analysis, two-dimensional infra-red correlation spectroscopy, 2DCOS-IR, and differential scanning calorimetry (DSC). It was found that both chain scission and crosslinking yields were decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…We propose to limit crystal growth during steam exposure by reducing the polymer chain mobility through chemical crosslinking. Many methods have been reported for preparing crosslinked PAEKs through thermal annealing, electron and ion irratiation, and chemical modification . In our preliminary attempt to hinder the crystal growth in PEKK during steam exposure, we investigated the steam stability of ketimine crosslink chemistry reported previously for PEEK .…”
Section: Introductionmentioning
confidence: 99%
“…We propose to limit crystal growth during steam exposure by reducing the polymer chain mobility through chemical crosslinking. Many methods have been reported for preparing crosslinked PAEKs through thermal annealing, electron and ion irratiation, and chemical modification . In our preliminary attempt to hinder the crystal growth in PEKK during steam exposure, we investigated the steam stability of ketimine crosslink chemistry reported previously for PEEK .…”
Section: Introductionmentioning
confidence: 99%
“…The important spectral features of semicrystalline PET include the aromatic and aliphatic –C‐H bond stretching at 3100 to 2800 cm −1 , the ester carbonyl bond and the ester group stretching at 1710 and 1300 cm −1 respectively and the methylene group at 1100 cm −1 . Many of the remaining bands are sensitive to configuration of the ethylene glycol group ( gauche / trans isomers) and also phenylene carbonyl bonds ( cis –trans isomers), and thus they depend on the preparation method of the sample …”
Section: Resultsmentioning
confidence: 99%
“…These bands have been used to follow the changes in molecular structure on ageing, and a change from trans to gauche conformations of the ethylene units in PET has been reported . On the other hand, Schmidt has shown that the intensity of an absorption band is governed by a configurational or structural factor and an orientation factor. He found that both trans and gauche forms in the amorphous phase of PET increased with increasing the degree of orientation.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, these defects can lead to the formation of small molecular products, accumulation of volatile products; crosslinking and chain scissioning . The chain scission and crosslinking effects can determine the decomposition extent in the materials . Hence, there is a crucial need to understand the behavior of these materials once exposed to high‐energy radiations.…”
Section: Introductionmentioning
confidence: 99%
“…5 The chain scission and crosslinking effects can determine the decomposition extent in the materials. 6 Hence, there is a crucial need to understand the behavior of these materials once exposed to high-energy radiations.…”
Section: Introductionmentioning
confidence: 99%